Human Theory of Mind Inference in Search and Rescue Tasks. (September 2021) - Li, Huao; Zheng, Keyang; Lewis, Michael; Hughes, Dana; Sycara, Katia
The ability to make inferences about other's mental state is referred to as having a Theory of Mind (ToM). Such ability is the foundation of many human social interactions such as empathy, teamwork, and communication. As intelligent agents being involved in diverse human-agent teams, they are also expected to be socially intelligent to become effective teammates. To provide a feasible baseline for future social intelligent agents, this paper presents a experimental study on the process of human ToM reference. Human observers' inferences are compared with participants' verbally reported mental state in a simulated search and rescue task. Results show that ToM inference is a challenging task even for experienced human observers.